AGRICULTURE AND SOCIO-ECONOMIC CHANGE IN THE REGION OF MSELLATA, TRIPOLITANIA - J. M. Hilal (Dirasat in Economics and Business, 1969)
Olive cultivation in Msellaía has been the tradition al of livelihood for a long period of time, probablv since the Roman period. In 1964, the area had approximately 140,000 producing olive trees. That is, an average of 10 trees per head Further- ;nost olive F.arde\žs are also sown with cereals. The distribution of land in the area averaged (in 1964) 10 hectares per household l . Most of the land is usually sown with barley and the rest with wheat. Barley is sown between October and January and harvested in April or M ay. It is cultivated for domestic and animal consumption, and as a cash crop